Increased Winter‐Mean Wave Height, Variability, and Periodicity in the Northeast Atlantic Over 1949–2017. Issue 8 (24th April 2018) - Castelle, Bruno; Dodet, Guillaume; Masselink, Gerhard; Scott, Tim
Abstract: A 69‐year (1948–2017) numerical weather and wave hindcast is used to investigate the interannual variability and trend of winter wave height along the west coast of Europe. Results show that the winter‐mean wave height, variability, and periodicity all increased significantly in the northeast Atlantic over the last seven decades which primarily correlate with changes in the climate indices North Atlantic Oscillation (NAO) and West Europe Pressure Anomaly (WEPA) affecting atmospheric circulation in the North Atlantic. NAO and WEPA primarily explain the increase in winter‐mean wave height and periodicity, respectively, while both WEPA and NAO explain the increase in interannual variability. This increase in trend, variability, and periodicity resulted in more frequent high‐energy winters with high NAO and/or WEPA over the last decades. The ability of climate models to predict the winter NAO and WEPA indices a few months ahead will be crucial to anticipate coastal hazards in this region. Plain Language Summary: We explore the evolution of winter‐mean wave height, variability, and periodicity in the northeast Atlantic over 1949–2017 and the links with the primary climate indices explaining winter wave activity, which is critical from the coastal hazard perspective. The climate indices NAO and WEPA primarily drive the increase in winter‐mean wave height and periodicity, respectively, while both WEPA and NAO explain the increase in interannual variability, resulting in more frequent high‐energy winters over the last seven decades. Extreme winter‐mean wave heights become more frequent as WEPA and NAO positivity and variability increase. Predicting WEPA and NAO a few months ahead is crucial to anticipate coastal hazards, which is of interest for coastal and climate communities. Key Points: The combination of the NAO and WEPA indices controls winter‐mean wave height trend and variability along the entire west coast of Europe Winter‐mean wave height, variability, and periodicity all increased over the last seven decades Extreme winter‐mean wave heights become more frequent as WEPA and NAO positivity and variability increase